ZRP cadet recruitment system - Mugari, Xaviour (Midlands State University, 2017)
The main aim of this project was to develop a computerised online Zimbabwe Republic Police (ZRP) Recruitment System that will store information of every applicant and be able to process, evaluate and produce feedback to the applicants efficiently and manipulation of information. Officer recruitment at ZRP was facing problems with the manual filing system that they were using to store information, and hence processing of applications and evaluation was now a tedious and unfair process. So the purpose of the project was to develop computerized system that would cater for these needs. Information on the requirements of the recruiting staff was gathered through various Information Gathering Methodologies such as interviews, questionnaires and observations. It was noted that the system allowed too much access to confidential documents and that the recruiting staff were working under hectic schedules. Also it took time for the applicant to receive feedback about his/her application after application processing was done. After the requirements were gathered, the proposed system was designed. A range of Microsoft tools most notably Visual Studio 2012 which comprises of Visual Basics.Net were used to develop the system. Also a MySQL server database managed by Windows Server 2008R2 operating system was used to store the large volumes of information and redundancies were kept under control while information security was upgraded. Testing and final installation of the hardware and software at the implementation phase made sure that the developed system was fully functional and operational as well as those activities associated with turning over control of the new system to the end users. The finished system was implemented under a pilot run change over on recommendation by the Developer. It was successful and faced little problems. Users were trained to use the system effectively and the system was fully operational. Regular maintenance was chosen for the system but other maintenance methods such a adaptive were recommended so as to keep the system up to date with its environment. In conclusion the research study was a success. The developer made recommendations on future studies and on improving the study he made. Upon completion of the project, there was improved process efficiency, quality of service, convenience to management and applicants at ZRP.